IMG-18. ASSESSMENT OF SUSPECTED DISEASE PROGRESSION USING MULTIPARAMETRIC 18F-CHOLINE PET/MRI IN CHILDHOOD AND TEENAGE-YOUNG ADULT GLIOMAS. (4th December 2020) - Ferrazzoli, Valentina; Shankar, Ananth; Cockle, Julia; Tang, Christine; Al-khayfawee, Ahmed; Thomas, Benjamin; Barnes, Anna; Bomanji, Jamshed; Fraioli, Francesco; Hyare, Harpreet
Abstract: OBJECTIVES: Evaluation of post-treatment glioma burden remains a significant challenge in children, teenagers and young adults (TYA). The aim of this study was to evaluate the utility of ChoPET/MRI for evaluation of suspected disease progression in childhood and TYA gliomas. METHODS: 27 patients (mean age 14 years, range 6–21 years) with suspected glioma disease progression were evaluated with ChoPET/MRI (n=59). Relative cerebral blood volume (rCBV), apparent diffusion coefficient (ADC) and maximum standardised uptake values (SUVmax ) in enhancing (enh) and non-enhancing (ne) tumour and normal-appearing white matter (wm) were calculated (rCBVenh, rCBVne, rCBVwm, ADCenh, ADCne, ADCwm, SUVenh, SUVne, SUVwm ). 2 blinded radiologists scored tumour probability (1 = unlikely; 5 = definitely). Sensitivity and specificity calculated with gold standard histopathology or clinical follow-up. RESULTS: Accuracy for the detection of residual/recurrent tumour on conventional MRI was 96.3% (91.7% ≤14 years, 100% ≥15 years) and ChoPET was 73.1% (66.7% ≤14 years, 80.0% ≥15 years). Lack of agreement was observed in 9/27 patients, with ChoPET superior to MRI in 1 case of a posterior fossa tumour. Tumour component analysis demonstrated significantly higher SUVenh and SUVne than SUVwm (SUVenh : p<0.001; SUVne : p=0.004, equivalent to results were observed for ADV and rCBV (ADCenh, ADCne : p<0.001 vs ADCwm ; rCBVenh, rCBVne : p<0.001 vs rCBVwm ). CONCLUSIONS: MRI is more sensitive than ChoPET in the evaluation of suspected disease progression in TYA gliomas. However, quanititative ChoPET is able to detect enhancing and non-enhancing tumour and may be helpful in evaluating posterior fossa disease where MRI is equivocal.